THE USE OF MULTIMEDIA INTERACTIVE DEVICE OF EPRESENTER IS IN TEACHING OF MATHEMATICS - E. Dobroshtan (Kherson State University, 2011)
The use of multimedia interactive device of eRresenter is examined in teaching of mathematics as will build on for studies and presentation.